2012
DOI: 10.5539/jsd.v5n7p18
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Facility Location – A Literature Review

Abstract: Facility location methods play a crucial role in specifying the optimum location options for various types of facilities. A question that arises is what makes a facility location decision a sustainable one? Facility location, also known as location analysis, is a known concept in the literature, but sustainable facility location is not. This requires appropriately defining the concept and framing the problem in order to address the relevant issues. Facility location models in the existing literature do not eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…Terouhid et al (2012) found 38 papers in their review, focusing on location and siting models. Therefore, it is timely to conduct a broad analysis of the state of the art on sustainability aspects related to manufacturing facility location, by providing a systematic literature review, synthesize the findings into a framework and identifying areas for future research.…”
Section: ) and Procter And Gamble (mentioning
confidence: 99%
See 1 more Smart Citation
“…Terouhid et al (2012) found 38 papers in their review, focusing on location and siting models. Therefore, it is timely to conduct a broad analysis of the state of the art on sustainability aspects related to manufacturing facility location, by providing a systematic literature review, synthesize the findings into a framework and identifying areas for future research.…”
Section: ) and Procter And Gamble (mentioning
confidence: 99%
“…Therefore, it is timely to conduct a broad analysis of the state of the art on sustainability aspects related to manufacturing facility location, by providing a systematic literature review, synthesize the findings into a framework and identifying areas for future research. In this review, we perform an independent and structured search strategy with a broader focus than Terouhid et al (2012) and identify 81 papers (with only one common paper; Dou and Sarkis, 2010). We include both quantitative 4 and qualitative research.…”
Section: ) and Procter And Gamble (mentioning
confidence: 99%
“…In the future, firms should turn performance improvements through sustainable manufacturing into a competitive weapon, reducing environmental harm and stimulating social solidarity (Kleindorfer et al, 2005). When compared with past practice, not only industry and government but also the general public are demanding more sustainable manufacturing processes and systems that satisfy economic and environmental goals (Terouhid et al, 2012).…”
Section: Sustainable Manufacturing E a Future Challenge In Emerging Mmentioning
confidence: 99%
“…The Tidal Turbine Location Problem (TTLP), which is the focus of this paper, constitutes a new extension to the classical Facility Location Problem (FLP) in operations research, which possesses an extensive literature spanning several decades; for reviews of variants, mathematical models, and solution methods of the FLP, see (Aikens, 1985;Owen & Daskin, 1998;ReVelle & Eiselt, 2005;Şahin & Süral, 2007;Melo et al, 2009;Farahani et al, 2010;Aras et al, 2012;Beltrán-Royo et al, 2012;Farahani et al, 2012;Terouhid et al, 2012;Drezner, 2013;Öncan, 2013;Stanimirović, 2013). There have been numerous extensions to and variants of the FLP reflecting the specific application environment under consideration.…”
Section: Introductionmentioning
confidence: 99%